2019
DOI: 10.1037/pne0000171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ascorbic acid combined to environmental enrichment on anxiety and memory.

Abstract: Ascorbic acid (AA; vitamin C) is an important antioxidant that is directly involved in regulating physiological and psychological systems such as anxiety, memory, depression, stress, and emotional mood states. Environmental enrichment (EE) studies in animals have shown improvements in anxiety and memory as measured by behavioral experiments from living in improved settings. In the present study, the influences of AA and enriched environments were explored in 13-month-old rats, considered middle-aged, half of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…Regression analysis in WT males revealed that hippocampal ascorbate, FAD, and PA might mediate spatial memory retention in the second probe trial (72 h after the last hidden-platform training). This result is consistent with the antioxidant properties of ascorbate, the proposed vitamin C depletion caused by environmental smoking (Preston et al 2003), and the relationship of ascorbate with spatial memory in the water maze (de Oliveira et al 2019).…”
Section: Environmental Health Perspectivessupporting
confidence: 88%
“…Regression analysis in WT males revealed that hippocampal ascorbate, FAD, and PA might mediate spatial memory retention in the second probe trial (72 h after the last hidden-platform training). This result is consistent with the antioxidant properties of ascorbate, the proposed vitamin C depletion caused by environmental smoking (Preston et al 2003), and the relationship of ascorbate with spatial memory in the water maze (de Oliveira et al 2019).…”
Section: Environmental Health Perspectivessupporting
confidence: 88%